Seroprevalence of antibodies to Brucella sp in goats Malargüe department , Mendoza (Veterinary Science, 2017)
A survey was carried out in 1200 goats from 16 farms situated in the Malargüe district (province of Mendoza) through Buffer Plate Antigen (BPA). The seropositive were exposed to seroagglutination in Wright tube (SAT) and 2-Mercaptoethanol to verify the presence of resistant antibodies. 3.83% serologic positive animals was obtained
Keywords: Brucellosis; goats